Dabrafenib and trametinib treatment-associated fevers in metastatic melanoma causing extreme elevation in procalcitonin in the absence of infection. Issue 8 (September 2018) - Clay, Timothy D.; Bowyer, Samantha E.
Abstract : Febrile illnesses are common in the management of metastatic solid organ malignancies. Traditionally they occur in the setting of immunosuppression and neutropenia owing to cytotoxic therapy necessitating consideration of systemic infections. Systemic markers of inflammation, such as C-reactive protein and procalcitonin (PCT), may be used to assist in determining the aetiology of a fever in such patients. Newer anticancer therapies may cause significant noninfectious fevers and may result in a rise in inflammatory markers, despite the absence of an infection. We present a case of a critically unwell febrile patient being treated with dabrafenib and trametinib for advanced melanoma. The patient had an extreme elevation in PCT in the absence of infection. We discuss the presentation of fevers related to dabrafenib and trametinib therapy in the management of advanced melanoma, and the utility of PCT in the management of fevers in advanced solid organ malignancies.